A randomised controlled trial of etanercept and methotrexate to induce remission in early inflammatory arthritis: the EMPIRE trial. Issue 6 (11th March 2014) - Nam, J L; Villeneuve, E; Hensor, E M A; Wakefield, R J; Conaghan, P G; Green, M J; Gough, A; Quinn, M; Reece, R; Cox, S R; Buch, M H; van der Heijde, D M; et al.
Abstract : Objective: To compare the efficacy of etanercept (ETN) and methotrexate (MTX) versus MTX monotherapy for remission induction in patients with early inflammatory arthritis. Methods: In a 78-week multicentre randomised placebo-controlled superiority trial, 110 DMARD-naïve patients with early clinical synovitis (≥1 tender and swollen joint, and within 3 months of diagnosis) and either rheumatoid factor, anticitrullinated protein antibodies or shared epitope positive were randomised 1:1 to receive MTX+ETN or MTX+placebo (PBO) for 52 weeks. Injections (ETN or PBO) were stopped in all patients at week 52. In those with no tender or swollen joints (NTSJ) for >26 weeks, injections were stopped early. If patients had NTSJ >12 weeks after stopping the injections, MTX was weaned. The primary endpoint was NTSJ at week 52. Results: No statistically significant difference was seen for the primary endpoint (NTSJ at week 52 (32.5% vs 28.1% [adjusted OR 1.32 (0.56 to 3.09), p=0.522]) in the MTX+ETN and MTX+PBO groups, respectively). The secondary endpoints did not differ between groups at week 52 or 78. Exploratory analyses showed a higher proportions of patients with DAS28-CRP<2.6 in the MTX+ETN group at week 2 (38.5% vs 9.2%, adjusted OR 8.87 (2.53 to 31.17), p=0.001) and week 12 (65.1% vs 43.8%, adjusted OR 2.49 (1.12 to 5.54), p=0.026). Conclusions: In this group of patients with early inflammatory arthritis, almost a third had no tender, swollen joints after 1 year. MTX+ETN was not superior to MTX monotherapy in achieving this outcome. Clinical responses, however, including DAS28-CRP<2.6, were achieved earlier with MTX+ETN combination therapy. Trial registration number: The EMPIRE trial is registered on the following trial registries: Eudract-2005-005467-29; ISRCTN 55428162 (http://www.controlled-trials.com/ISRCTN55428162 /EMPIRE). The full trial protocol can be obtained from the corresponding author.